2018
DOI: 10.1016/j.jos.2017.10.015
|View full text |Cite
|
Sign up to set email alerts
|

State-of-the-art transforaminal percutaneous endoscopic lumbar surgery under local anesthesia: Discectomy, foraminoplasty, and ventral facetectomy

Abstract: Transforaminal (TF) percutaneous endoscopic surgery for the lumbar spine under the local anesthesia was initiated in 2003 in Japan. Since it requires only an 8-mm skin incision and damage of the paravertebral muscles would be minimum, it would be the least invasive spinal surgery at present. At the beginning, the technique was used for discectomy; thus, the procedure was called PELD (percutaneous endoscopic lumbar discectomy). TF approach can be done under the local anesthesia, there are great benefits. During… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
128
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 153 publications
(130 citation statements)
references
References 26 publications
2
128
0
Order By: Relevance
“…Recently, FELD for LDH was introduced by Yeung and Tsou, 6) and is gaining popularity with expanding adaptation for canal and foraminal stenosis. 3) The concept of FELD is based on minimal tissue damage, while achieving a favorable clinical outcome comparable with conventional open surgery. 4,5) Patients are expected to have less back pain, shorter hospitalization, and a quicker return to daily activities compared with the conventional method.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, FELD for LDH was introduced by Yeung and Tsou, 6) and is gaining popularity with expanding adaptation for canal and foraminal stenosis. 3) The concept of FELD is based on minimal tissue damage, while achieving a favorable clinical outcome comparable with conventional open surgery. 4,5) Patients are expected to have less back pain, shorter hospitalization, and a quicker return to daily activities compared with the conventional method.…”
Section: Discussionmentioning
confidence: 99%
“…Yeung et al (25) reported the long-term clinical results and more than 80% would be excellent and good. Next, TF full-endoscopic lateral recess decompression (TE-LRD) was started (16,17,18,26,27,28). Ahn et al (26) followed 45 patients who had the TE-LRD for years and reported satisfactory clinical results more than 80%.…”
Section: Discussionmentioning
confidence: 99%
“…After the wound was rinsed, the fenestrated brous ring was repaired by electrocoagulation. The working cannula was then removed, and the incision was closed [13].…”
Section: Operative Techniquementioning
confidence: 99%